C# essentials - Albahari, Ben (O'Reilly, 2001)
Concise but thorough, C# Essentials introduces the brand-new Microsoft C# programming language and the Microsoft .NET Common Language Runtime (CLR) and Base Class Libraries (BCL) that support it. The compact format and terse presentation of key concepts serve as a roadmap to the online documentation included with the Microsoft .NET Framework SDK; the many examples provide much-needed context. In addition to overviews of C#, the CLR, and the BCL, C# Essentials includes coverage of: Every C# language element and its syntax, in reference format The major C# datatypes, with code examples Basic C# programming tasks Interoperations with legacy Win32 APIs and COM components, and the use of C/C++ style pointers within the managed context of the CLR. C# Essentials is an inexpensive way for experienced programmers to get up to speed quickly on the language best suited to developing web applications and services on the new Microsoft .NET platform.